(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2016)
Background. Nowadays there are lots of treatment methods in medicine which can help to solve biosocial problems of patients. Mobilization with movement of vertebral spines is a safer technique compared to manipulative techniques. Due to the prevailing public opinion and feedback about the fast effect, manual therapy is becoming increasingly popular and demanded. Spinal mobilization with movement, compared with the manipulative techniques is a safe and “soft” treatment technique, which is comfortable for the patient and attractive for physiotherapist due to little time and tools cost for the procedure, but there is still a lack of suffcient data on the effectiveness of this method. The aim of research was to evaluate the effect of mobilization with movement on non-specifc neck pain, and patient’s functional activity. Methods. The sample consisted of 30 patients with mean age of 50.2 ± 9.57 years. The main criteria for sample selection was neck pain without any structural changes diagnosed. Patients were informed about research process, treatment method and possibilities of biological responses. We used numeric pain rating scale (NPRS) to assess pain, and patient’s specifc functional scale (PSFS) – to assess functional activity. Treatment duration was one week. Cervical spine mobilization with movement was performed 3 times, every second day, with 10 repeated movements. Results. After the applied treatment the patients’ neck pain intensity decreased statistically signifcantly (from 5.9 ± 1.3 to 2.36 ± 1.16 points) and functional activity of patients improved signifcantly (from 3.95 ± 1.37 to 7.37 ± 1.18 points). Conclusion. Mobilization with movement statistically signifcant decreased intensity of neck pain and improved functional activity of patients. Keywords: neck pain, mobilization with movement, pain assessment scale, patient’s specifc functional scale.